Invisible manuscripts: textual scholarship and the survival of 2 Baruch - Lied, Liv Ingeborg (Studien und Texte zu Antike und Christentum, 2021)
In this critical exploration of the role of manuscripts in textual scholarship, Liv Ingeborg Lied studies the Syriac manuscript transmission of 2 Baruch. These manuscripts emerge as salient sources to the long life of 2 Baruch among Syriac speaking Christians, not merely witnesses to an early Jewish text. Inspired by the perspective of New Philology, Lied addresses manuscript materiality and paratextual features, the history of ownership, traces of active readers and liturgical use, and practices of excerption and re-identification. The author's main concerns are the methodological, epistemological and ethical challenges of exploring early Jewish writings that survive only in Christian transmission. Through engagement with the established academic narratives, she retells the story of 2 Baruch and makes a case for manuscript- and provenance-aware textual scholarship